Attitude towards the COVID-19 vaccine in residents of the Guerrero State, México - Alcocer-Carranza, Jesús; Gonzalez-Carlo, Ana Lizzeth; Reyna-Avila, Leticia; Peña-Marcial, Elvia; Pérez-Cabañas, Rodrigo (Universidad y Salud, 2022)
Introduction: Vaccines have become a promising solution to mitigate COVID-19. However, it faces important challenges, including people’s attitude towards this new therapeutic. Objective: To determine the attitude of the inhabitants of the Guerrero State (Mexico) towards the vaccine to mitigate COVID-19. Materials and methods: Quantitative, non-experimental, descriptive, and cross-sectional research was conducted using a conglomerate-type sampling method. The sample included 296 people from the different regions of the State. The study included participants who were older than 18 years of age and expressed their desire to participate through the informed consent. Questionnaires in Google were used for data collection. The scale to determine the attitude towards COVID-19 vaccine contained two sections: sociodemographic data and attitude towards the vaccine. The last section was subdivided into cognitive, subjective, and behavioral (which includes cognitive and subjective) dimensions. The instrument had 25 items with closed answer options on a Likert-type scale. Results: The attitude towards the COVID-19 vaccine is predominantly negative (52.70%) in the population from Guerrero. Conclusions: The behavioral dimension could be considered a predictor of acceptance towards the COVID-19 vaccine.